Origins, visions and contributions of Filipino educational leaders a paradigm of visionary leadership - Carillo, Clarita M. De Leon (2005)
This qualitative study was undertaken to evolve a paradigm of visionary leadership through the analysis of the origins, visions, and contributions of selected Filipino leaders in education. The contents that emerged pertinent to the formation stage included family values, childhood experiences, socio-economic milieu, and educational trends. The accession stage consisted of leadership enablers. Particular to the incumbency stage were the leaders' goal-achievement functions and group-maintenance functions. The recurring themes or patterns in the educational philosophy of these leaders were reconstructionism, pragmatism, and idealism. All the findings were integrated into a Four-P Paradigm of Visionary Leadership - Purpose, Practice, Product and Parameter.